The front-end web developer bootcamp : HTML, CSS, JS and React. (Manning Publications, 2023)
Are you interested in learning the skills and tools required to create modern, interactive, and responsive websites? The Front-End Web Developer Bootcamp is the course for you! In this comprehensive bootcamp, you'll learn HTML, CSS, JavaScript, and React--the building blocks of the web--and gain hands-on experience making dynamic and engaging web pages from scratch. This course is designed for beginners who want to pursue a career in web development or simply want to learn how to create beautiful and functional websites. You'll learn what the different tools can do, and then work on a series of projects so you can practice your new knowledge and skills. By the end of the course, you'll have a portfolio of projects to showcase your skills to potential employers or clients. In this course, you will: Gain in-demand skills Front-end web development is a highly sought-after skill in today's job market. By mastering HTML, CSS, JavaScript, and React, you'll be well-positioned to land a job in a rapidly growing field. Learn from expert instructors Our experienced instructors have years of experience in the field and are passionate about sharing their knowledge with you. They created this course to help you progress at your own pace and achieve your goals. Practice with hands-on learning The best way to learn front-end web development is through hands-on experience. This course emphasizes practical projects that simulate real-world scenarios. You'll come away with a solid understanding of the tools and techniques used by professional web developers. Build a portfolio As you complete projects throughout the course, you'll build a portfolio of work that showcases your skills to potential employers or clients. This portfolio will demonstrate your ability to create responsive and engaging websites, which is essential in today's job market.